ANALISIS MAKRO EKONOMI DAN PASAR KEUANGAN GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN - Mulyadi, Mulyadi; Permata, Irma Sari (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aimed to analyze the correlation between Macroeconomics Variable and Global Financial Markets on Composite Stock Price Index in Indonesia Stock Exchange in 2012 – 2019 partially and simultaneously. Design/methodology/approach- This study used secondary data with multiple linear regression analysis methods. Macroeconomics Variable is proxied by Inflation, SBI Rate, and Exchange Rate IDR/USD to be juxtaposed with Global Financial Markets Variable proxied by Malaysia, Singapura, Filipina, and Australia index. Findings- The results showed that Inflation and SBI Rate partially negative effect on CSPI. Straits Times Index, Philippine Stock Exchange Index, and Australian Securities Exchange 200partially positive effect on CSPI. Meanwhile, Exchange Rate IDR/USD and Kuala Lumpur Stock Exchange partially have no effect on CSPI. Simultaneously, all the variables have a significant effect by influencing by 92.9% while 7.1% is explained by other variables not examined in this study. Implications- For investors who want to invest in the Indonesian capital market need to pay attention to Macroeconomics in Indonesia and related foreign exchanges. Based on the results of research that has been carried out, it is proven that these variables have various effects, either significant or insignificant, on the Composite Stock Price Index. Keywords: Composite Stock Price Index, Global Financial Stock Index, Macroeconomics Variable